Telomere Signaling and Maintenance Pathways in Spermatozoa of Infertile Men Treated With Antioxidants: An in silico Approach Using Bioinformatic Analysis - Panner Selvam, Manesh Kumar; Baskaran, Saradha; Sikka, Suresh C. (Frontiers in Cell and Developmental Biology, 2021)
Telomere shortening is considered as a marker of cellular senescence and it is regulated by various signaling pathways. Sperm telomere appears to play important role in its longevity and function. Antioxidant intake has been known to prevent the shortening of telomere. In the management of male infertility, antioxidants are commonly used to counterbalance the seminal oxidative stress. It is important to understand how antioxidants treatment may modulate telomere signaling in sperm. In the current study, we have identified 377 sperm proteins regulated by antioxidants based on data mining of published literature. Bioinformatic analysis revealed involvement of 399 upstream regulators and 806 master regulators associated with differentially expressed sperm proteins. Furthermore, upstream regulator analysis indicated activation of kinases (EGFR and MAPK3) and transcription factors (CCNE1, H2AX, MYC, RB1, and TP53). Hence, it is evident that antioxidant supplementation activates molecules associated with telomere function in sperm. The outcome of this in silico study suggests that antioxidant therapy has beneficial effects on certain transcription factors and kinases associated with sperm telomere maintenance and associated signaling pathways that may play an important role in the management of male factor infertility.